Tingkat Literasi Terkait Kewajiban Pembayaran Pajak Pada Masyarakat Kota Binjai Sumatera Utara - Anggi Luthfiah Pane; Nurlaila Rachman; Triana Triana (Pajak dan Manajemen Keuangan, 2024)
The study tested tax literacy and factors that influenced tax compliance in Binjai City, North Sumatra, using a qualitative approach of semi-structured interviews and observations. The results show that the majority of people have a basic understanding of tax types, but difficulties in understanding technical details such as tax calculations and reporting processes. Factors such as education, income, and tax administration experience affect tax literacy, while awareness of the importance of tax for development still needs to be enhanced. The implications of this research include recommendations to develop inclusive and tailor-made tax education programmes, to enhance public understanding and compliance in paying taxes and to support national development effectively. This research makes an important contribution to local tax policy in an effort to increase public participation and awareness of their tax obligations.